PERAN MANAJEMEN SEKOLAH DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN PENDIDIKAN DI ERA DIGITAL - Mahmud Hasibuan, Amir; Nazwi Haliza Purba; Niko Alriadi Sinaga; Putri Adhelia Br Damanik; Rahmayani (Jurnal Merah Putih Sekolah Dasar, 2025)
This article aims to analyze the role of management in improving the effectiveness of educational management in schools. The study was conducted using a literature review approach, examining a number of journals and previous research relevant to the topic of educational management. The analysis shows that management plays a central role in creating an effective, efficient, and sustainable education system. Careful planning, visionary leadership of the principal, professional human resource management, and the implementation of continuous supervision and evaluation are the keys to successful educational management. Furthermore, collaboration between schools and the community, as well as the use of digital technology, contribute to strengthening the effectiveness of educational management in the modern era. Thus, effective management is not only oriented towards administrative aspects, but also emphasizes the dimensions of leadership, participation, and innovation in achieving optimal educational quality.